Detecção e leitura de QR Codes em imagens - Pendiuk, Guilherme Francisco Iakmiu (2015)
QR Codes are bidimensional barcodes utilized to store bigger messages than ordinary bar codes can hold. In this work, an algorithm is proposed for QR Codes detection in images with different characteristics, besides its reading according methods proposed by the norm that sets patterns for these kinds of codes. For such, becomes necessary the image import, so the algorithm can detect the main characteristic of the code: the three location markers. Then, the QR Code must be cut off of the image so the algorithm can perform the reading step. All this process is made using MATLAB® as its development platform. In the end, some results show that the algorithm can achieve its goals, as long as the code is not obstructed.